2023
DOI: 10.1371/journal.pone.0287145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fenbendazole on fecal microbiome in BPH/5 mice, a model of hypertension and obesity, a brief report

Abstract: Fenbendazole (FBZ) is a common antiparasitic treatment used in research rodent colonies for biosecurity purposes. The effect of this compound has been studied in C57 mice, but never before in a strain of mice that has co-morbidities, such as the blood pressure high (BPH)/5. The BPH/5 mouse is an inbred genetic model of hypertension. While both male and female BPH/5 have high blood pressure, there is a metabolic sexual dimorphism with females displaying key features of obesity. The obese gut microbiome has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Restricting the diet of the mice has the potential to place them in a negative energy balance which can allow for the development of adverse fetal outcomes including decreased nephron numbers, hypertension, proteinuria, or renal dysfunction after birth ( Luyckx, 2020 ). While excessive dietary restriction can be harmful, the method of food restriction utilized, pair feeding, which is matched to lean, gestation-matched control mice, acts to normalize obese BPH/5 mice weight and adiposity, and serum leptin by e7.5 ( Reijnders et al, 2019 ), and has demonstrated improvement in fetal and maternal outcomes ( Beckers et al, 2023 ). Pair-feeding BPH/5 showed a similar reduction in serum leptin by e7.5 (83%) as by e18.5 (95%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Restricting the diet of the mice has the potential to place them in a negative energy balance which can allow for the development of adverse fetal outcomes including decreased nephron numbers, hypertension, proteinuria, or renal dysfunction after birth ( Luyckx, 2020 ). While excessive dietary restriction can be harmful, the method of food restriction utilized, pair feeding, which is matched to lean, gestation-matched control mice, acts to normalize obese BPH/5 mice weight and adiposity, and serum leptin by e7.5 ( Reijnders et al, 2019 ), and has demonstrated improvement in fetal and maternal outcomes ( Beckers et al, 2023 ). Pair-feeding BPH/5 showed a similar reduction in serum leptin by e7.5 (83%) as by e18.5 (95%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown inadequate spiral artery formation and smaller placental vessel area in BPH/5 placenta compared to C57 mice (Dokras et al, 2006). Furthermore, maternal weight loss and reduced leptin have been associated with prevention of FGR in this model (Beckers et al, 2023). To better understand the impact of hypoxia and pair-feeding on fetoplacental development, the placental vessel area in ad lib and pair-fed BPH/5 e18.5 placenta were assessed.…”
Section: Decidual Hypoxia Gene Expression In Bph/5 Is Sensitive To Le...mentioning
confidence: 97%
See 1 more Smart Citation